2009
DOI: 10.2174/138955709791012229
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Postoperative Cognitive Dysfunction (POCD)

Abstract: POCD describes a decline in cognitive function after surgery with a predominance in the elderly patient. Although there is general agreement that POCD is likely to be multifactorial, whether its occurrence is a result of the effects of surgery or general anesthesia remains unclear. This review provides a synopsis of the available clinical and preclinical data and summarizes recent research relevant to the occurrence of POCD and possible pharmacologic algorithms for its prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 2 publications
0
39
0
3
Order By: Relevance
“…Since general anesthesia is needed for esophageal dilation procedures, and 5–10% of our study patients needed several procedures, the possibility of long-term sequelae of repeated anesthesia in young children should be considered [8, 9]. However, studies with long follow-ups that evaluated the cognitive dysfunction of patients undergoing repeated dilations of AS after EA reconstruction have not been reported and are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Since general anesthesia is needed for esophageal dilation procedures, and 5–10% of our study patients needed several procedures, the possibility of long-term sequelae of repeated anesthesia in young children should be considered [8, 9]. However, studies with long follow-ups that evaluated the cognitive dysfunction of patients undergoing repeated dilations of AS after EA reconstruction have not been reported and are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…3 The aetiology of POCD is complex: age, preoperative low baseline cognition, limited education and type of surgery may contribute to its occurrence. 4 Furthermore, the choice of anaesthetic drugs has also been alleged to affect cognitive function. 4 A number of animal studies have suggested a relationship between the inhaled anaesthetic administered and the development of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, the choice of anaesthetic drugs has also been alleged to affect cognitive function. 4 A number of animal studies have suggested a relationship between the inhaled anaesthetic administered and the development of dementia. [5][6][7][8] Sevoflurane anaesthesia impaired spatial learning and memory in aged rats through an effect on amyloid b peptide oligomerization and deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O diagnóstico de DCPO não é de fácil execução porque não há sintomas clínicos aparentes ---os pacientes podem apresentar uma deficiência em uma ou várias habilidades cognitivas, como na memória, atenção, concentração, velocidade da resposta motora e mental, no processamento de informações e aprendizado após a cirurgia e a anestesia, que são diferentes de delírio. 4,13,19 A manifestação é sutil, geralmente muitos dias ou semanas após a cirurgia. 2,4 Grande parte dos médicos não consegue reconhecer o declínio cognitivo do paciente logo após a cirurgia; os próprios pacientes podem não estar cientes de seu DCPO ou relutarem em relatar qualquer alteração devido à falta de atenção ou constrangimento.…”
Section: Introductionunclassified